Effects of intercropping hyperaccumulators on growth and cadmium accumulation of water spinach (Ipomoea aquatica Forsk). Issue 5 (8th April 2020) - Tang, Yi; Liao, Jichao; Yu, Xuena; Li, Huanxiu; Lin, Lijin; Liao, Ming'An; Wang, Zhihui; Xiong, Bo; Sun, Guochao; Wang, Xun; Liang, Dong; Xia, Hui; et al.
ABSTRACT: A pot experiment was conducted to study the effects of intercropping with the cadmium (Cd) hyperaccumulators Galinsoga parviflora, Bidens pilosa, Cosmos sulphureus and Solanum nigrum on the growth and Cd accumulation of water spinach ( Ipomoea aquatica Forsk). The results show that intercropping with B. pilosa improved biomass and photosynthetic pigment contents of water spinach, but intercropping with G. parviflora, C. sulphureus and S. nigrum shaded water spinach; thus, the growth of water spinach was inhibited. When compared with monoculture, the Cd contents in roots and shoots of water spinach were reduced by intercropping with B. pilosa, C. sulphureu s and S. nigrum, and the shoot Cd content decreased by 27.93%, 3.12% and 5.30%, respectively. Intercropping with G. parviflora reduced the root Cd content in water spinach, but increased the shoot Cd content. Therefore, intercropping with B. pilosa could promote the growth and reduce the Cd accumulation of water spinach.